Proteomic profile of pulmonary and extra pulmonary TB samples (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2018)
Introduction: Tuberculosis (TB) is a major health problem in India, so early diagnosis and treatment of Mycobacterium tuberculosis (M.tb.) infection can prevent deaths from this pathogen. The secretion of proteins by M.tb. is important in diagnostic purposes for generation of therapeutic drugs and vaccines candidates for TB. The objective of this study was to identify the protein expression (biomarkers) in TB and Tuberculosis meningitis (TBM) using proteomic approach.Methods: In this study, using Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDSPAGE), we analyzed the secretory proteins of M.tb. in serum, cerebrospinal fluid (CSF) samples. The identified proteins were determined by Total Lab- 100 Quantity One densitometry software.Results: Our study showed that protein bands expressed in CSF samples reveals the presence of 72kD, 70kD, 44kD, 40kD & 16kD predominantly in TBM patients compared to healthy individuals. The electrophoretogram identified 97kD, 72kD, 44kD, 38kD, 29kD & 16kD predominant proteins in serum samples of TB patients.Conclusion: The detection of secretory proteins in serum and CSF samples of M.tb. in TB and TBM patients gives reliable and early diagnosis of TB and TBM. The secretory proteins can be useful as immunodiagnostic and vaccine targets which can serve as important biomarkers